Retrospective and Systematic Analysis of Causes and Outcomes of Thrombotic Microangiopathies in Routine Clinical Practice: An 11-Year Study - Henry, Nicolas; Mellaza, Chloé; Fage, Nicolas; Beloncle, François; Genevieve, Franck; Legendre, Guillaume; Orvain, Corentin; Garnier, Anne-Sophie; Cousin, Maud; Besson, Virginie; Subra, Jean-François; Duveau, Agnès; et al. (Frontiers in Medicine, 2021)
Background. Thrombotic microangiopathies (TMA) are highly suspected in patients showing mechanical haemolytic anaemia, thrombocytopenia and haptoglobin consumption. Primary (thrombotic thrombocytopenic purpura (TTP) and atypical HUS (aHUS)) and secondary TMA are considered. Even if ADAMTS13 measurements and alternative complement pathway explorations have greatly improved the ability to identify primary TMA, their diagnosis remains difficult and their frequency relative to that of secondary TMA is undetermined. The objectives of the present study were therefore to describe the aetiologies, management and the outcomes of patients presenting with TMA in real-life clinical practice. Methods. We conducted a retrospective study between 01/01/2008 and 31/12/2018 that included all consecutive patients presenting with biological TMA syndrome at admission or developing during hospitalization. Patients were identified from the laboratory databases and their medical files were reviewed to confirm TMA diagnosis, to determine aetiology and to analyse their therapeutic management and outcomes. Results. During this period, 239 patients with a full TMA biological syndrome were identified and TMA diagnosis was finally confirmed in 216 (90.4%) after the cases were reviewed. Primary TMA (TTP or aHUS) were diagnosed in 20/216 patients (9.3%). Typical HUS was diagnosed in 8 patients (3.7%) and the most frequent secondary TMA were HELLP syndrome (79/216, 36.6%) and active malignancies (30/219, 13.9%). ADAMTS13 measurements and alternative complement pathway (cAP) analyses were performed in a minority of patients. Multiple factors identified as TMA triggers were present in most patients, in 55% of patients with primary TMA, versus 44.7% of patients with secondary TMA (p = 0.377). Death occurred in 57 patients (23.4%) during follow-up and dialysis was required in 51 patients (23.6%). Active malignancies (OR 13.7), transplantation (OR 4.43), male gender (OR 2.89) and older age (OR 1.07) were significantly associated with death. Conclusion. Secondary TMA represent a large majority of TMA causes in patients presenting a full TMA biological syndrome during routine clinical practice. Multiple factors favouring TMA are present in about half of primary or secondary TMA. ADAMTS13 and cAP were poorly explored in our cohort. The risk of death is particularly high in patients with malignancies as compared to patients with other TMA.